A Predictive Model for Determinants of Reproductive Behaviour in Şanlıurfa - Ayşe Taştekin; Şehadet Taşkın (Hemşirelikte Araştırma Geliştirme Dergisi)

(untitled)
Aim: This study aims to predict the determinants of current and future reproductive behaviour in Şanlıurfa.Material and Method: A cross-sectional study was conducted with 385 married women to examine the determinants of reproductive behavior. Data were collected with a survey form and evaluated with descriptive statistics and Structural Equation Model.Results: The mean age was 29.91 ± 7.41, the mean pregnancies number was 4.04 ± 2.35, the mean number children was 3.38 ± 1.87, and the mean ideal children number was 3.59 ± 1.64. 39.2% of the women did not want another child. Women's age (β=0.42), education status of women (β=-0.15), marriage age (β=-0.19), contraceptive failure (β=0.16), and the number of ideal children (β=0.34) were found to be the predictors of the current fertility. The number of ideal children (β=0.59), contraceptive failure (β=-0.14), and the number of children (β=-0.70) are the most important predictors of future fertility (p<0.05). Conclusion: As the number of women age and the ideal children number increases, the education level and marriage age decrease, and the children number increases. As the children number increases, the desire for future fertility decreases. The predictive model can guide the design, implementation, and evaluation of policies and programs for women's health professionals. More research is needed to examine how different factors affect current and future fertility.